Poverty Analysis of Children's Education Level in Paokmotong Village, Masbagik Sub-District - Pebrianti, Ruli; Aini, Qurratul; Mispandi, Mispandi; Juaini, Muhamad (IJE : Interdisciplinary Journal of Education, 2024)
This study aims to determine the Poverty Analysis of Children's Education Level in Paokmotong Village. This research uses a descriptive type of qualitative approach. The data collection techniques used by researchers are observation, interviews and documentation with 80 respondents to poor people in Paokmotong village. While the data analysis technique used is descriptive analysis technique through qualitative research, which uses data and information obtained directly from information then analyzed using the existing theoretical basis and obtained systematically based on facts in the field. The poverty experienced by the poor in Paokmotng Village has a wide impact on the level of education in the community. This can be seen in various aspects, namely employment or income, human resources, natural resources and government policies. From these various aspects, the impact of poverty is relative because each family has and feels a different impact from other families in the level of education, namely a low level of education